Alexander Dugin: Geopolitics at the Confluence of Theology, Tradition, and Eurasia - Mosbey, John Cody (Trinity College Dublin. School of Religion. Irish School of Ecumenics, 2020)
This dissertation examines the development and impacts of contemporary Russian Geopolitical-Theologian Alexander Dugin and his Fourth Political Theory. This study focuses through the receptive lenses of Western political and theological vantage points to examine how Dugin and his ideas are perceived in the West. Dugin is becoming a prominent figure and his anti-Western theory, his criticism of the West and Western Liberalism, and his evolution from a little-known activist to a controversial Geopolitical-Theologian are examined. His political theology and concepts of Liberal Democracy are also explored. Dugin claims to be a Traditionalist and a Eurasianist. In addition to discussing the features of both of these classifications, two major research strategies to examine and comment on these assertions are employed: first, Dugin is considered as an interpreter and commentator of the West; second, key observations, comments, critiques, and conclusions of selected Western interpreters and commentators on Dugin and his theory are reviewed. Data was collected from a variety of mostly Western sources: books, interviews, newspapers, journals, published reports, websites, and blogs. The methodology of this dissertation progresses topically with each of Dugin's claims, with the supporting evidence examined, first from Dugin's perspective, then from the standpoint of his commentators. In this process, Dugin's development of his Fourth Political Theory, his hermeneutical presuppositions, and the constituent elements of both are compared and contrasted. Conclusions reached recognize Dugin as a Neo-Traditionalist, a Neo-Eurasianist, and a Geopolitical-Theologian of significant force and impact. The effects of Dugin s theory are reflected in Russian governmental policy. Dugin's influence will, in turn, affect Western reception and reaction. The degree of this influence is difficult to predict; however, it is significant, portends potential World Power conflict, and demands attention and consideration.
APPROVED
Keywords: Alexander Dugin; Political Theology; Geopolitics; Traditionalism; Fundamentalism; Conspirology